Evaluation of complications after surgical treatment of benign prostatic hyperplasia - Kasimov S.S; Navruzov E.R (Academia One, 2023)
The article provides a comparative analysis of the results of the used methods of surgical treatment of patients with prostate adenoma. An assessment is made of the standardization of surgical interventions TUR of the BPH for adenoma as the “gold standard” in comparison with transvesical extraurethral adenomectomy. After TURP of the BPH, according to domestic and foreign authors, taking into account our own data, complications arise in total from 28.7 to 100% with non-radical removal of adenomotic (hyperplastic) tissues, and after extraurethral radical adenomectomy – 5.6% of cases. Thus, open transvesical, or retropubic, extraurethral adenomectomy is many times superior to “closed” transurethral resection of the prostate in terms of immediate and long-term results
Keywords: transurethral resection; extraurethral adenomectomy; prostate adenoma